Analysis of a cybersecurity architecture for satellites using model-based systems engineering (MBSE) approaches - Johnson, Daniel, author; Bradley, Thomas, advisor; Poturalski, Heidi, committee member; Adams, Jim, committee member; Herber, Daniel, committee member; Reising, Steve, committee member (Colorado State University. Libraries, 2025)
Historically, satellites have been relatively isolated from cybersecurity threats. However, during the 2020s, cyberattacks on critical ground-based infrastructure became more common and prevalent, and with the increase in technological advancement of peer adversaries, the United States government has come to recognize and define an increasing level of vulnerability in space-based assets as well. This doctoral research seeks to understand and address cybersecurity vulnerabilities inherent in commercial small-scale satellite architectures by demonstrating how model-based systems engineering (MBSE) can enable the design and analysis of a cyber-secure satellite architecture. To determine the cybersecurity vulnerabilities applicable to satellites, a scholarly review of literature on cybersecurity threats and mitigation techniques was performed and applied to satellite systems. The result of this scholarly review is an assessment of the cybersecurity threats applicable to satellites with a particular focus on small satellite architectures, and an understanding of current cybersecurity threat agents and the categories of cyber threats applicable to such satellites. Common architectures and satellite components were analyzed to determine vulnerabilities that could be exploited. The next phase of research then evaluated how industry has applied cybersecurity practices to satellite systems. We were able to determine the gaps which industry currently faces and recommended a set of generic requirements that could help create a cyber-secure satellite from early in the program lifecycle. The final phase of research synthesized the findings from the first two phases to build an MBSE model that integrates cybersecurity engineering and satellite architecture into a singular design process. We also analyzed the benefits to a company of applying the MBSE architectural process, paying particular attention to reusability of the model, cost, and human-centered benefits of committing to MBSE for multiple programs. A finding of this research is that the cybersecurity vulnerabilities for satellites are due to two main factors. First, as technology has advanced and become more available, there is a changing threat landscape where satellites launch is more accessible, increasing the risk that threat actors can compromise unprotected satellites. Second, space technology has lagged behind terrestrial information and cyber technology in its ability to adapt and overcome cybersecurity threats, creating vulnerabilities in satellite architectures. Another revelation is the disconnect between traditional software engineers and their cyber engineer counterparts, leading to a lack of understanding of key cyber-vulnerabilities during the design process. This leads to a consequential need to build cyber-protections into the design process from program initialization. Finally, the cyber tools in use today are also disconnected from the other traditional architectural design tools, leading to our conclusion that all of the tools must be integrated together under an MBSE design process, furthering the evolution of systems engineering while also encouraging the industry to incorporate cybersecurity into satellite programs from the beginning. Upon completion of this research project, the contributions are a scholarly review of the literature on cybersecurity threats and mitigation techniques in space and satellite systems, an evaluation of a set of cybersecurity requirements for satellite systems application, an MBSE example case for a cyber-security embedded satellite system, and an evaluation of the costs and benefits of an MBSE-enabled architecting process as applied to an industrial satellite system architecting process. The combination of this research represents novel contributions to the state of the field by defining the cybersecurity vulnerabilities for Space Systems and exhibiting how MBSE can aid in a cyber-secure architecting process.